The Effect of Family Economic Status, Peer Support, and Mass Media Perception on Career Planning of SMKS Students - Ar Byanfikas Musita; Awalya Awalya; Farid Ahmadi (Indonesian Journal of Guidance and Counseling: Theory and Application, 2026)
Career planning serves as a systematic framework that is essential to guides students toward a well-structured future. This study examines the effect of family economic status, peer support, and mass media perception on students' career planning. Utilizing a quantitative approach, this research sampled 222 students through proportionate stratified random sampling. The data involved were analyzed using hierarchical regression. The results of this study indicated that in Model 1, family economic status accounted for 27.3% of the variance in career planning (R2 = 0.273). The inclusion of peer support in Model 2 increased the contribution to 44.2% (R2 = 0.442); meanwhile the addition of mass media in Model 3 raised the total variance explained to 53.5% (R2 = 0.535). In addition, the t-test results confirmed that each additional variable group provided a statistically significant increase in the involved variables. The findings reveal that mass media, specifically the evaluating information dimension regarding the credibility and relevance of career-related data is the most dominant predictor of career planning among vocational high school students.